2018
DOI: 10.1177/0308518x18810002
|View full text |Cite
|
Sign up to set email alerts
|

Metropolitan governance structure and growth–inequality dynamics in the United States

Abstract: While much scholarly attention has long been paid to ways in which metropolitan areas are politically structured and operated to achieve a dual goal, economic growth and equality, relatively less is known about the complex relationship between metropolitan governance structures and growth-inequality dynamics. This study investigates how and to what extent metropolitan governance structures shape regional economic growth and inequality trajectories using the data for 267 US metropolitan areas from 1990 to 2010.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 67 publications
0
1
0
Order By: Relevance
“…Within metropolitan areas, government cooperation between cities and the spatial integration of the labor and housing markets are conducive to land use management [31,32]. However, cases from different fields worldwide have shown that socioeconomic contradictions and imbalances inevitably and universally exist within metropolitan areas [33][34][35][36][37][38][39]. Internal imbalance results in competition and conflict in land policy and development and brings new land use management challenges to metropolitan areas [40].…”
Section: Introductionmentioning
confidence: 99%
“…Within metropolitan areas, government cooperation between cities and the spatial integration of the labor and housing markets are conducive to land use management [31,32]. However, cases from different fields worldwide have shown that socioeconomic contradictions and imbalances inevitably and universally exist within metropolitan areas [33][34][35][36][37][38][39]. Internal imbalance results in competition and conflict in land policy and development and brings new land use management challenges to metropolitan areas [40].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, consistent with public health expenditure patterns, the proportions of these expenditures, except public welfare, had negative associations with political fragmentation. These findings suggest that individuals residing in a more fragmented county may not receive the same benefit from the social services spending, as well as public health expenditure, and the reduced spending may be associated with interjurisdictional competition that is likely to arise in a fragmented setting [42].…”
Section: Social Services Expendituresmentioning
confidence: 95%
“…Growing evidence exists of a disconnect between growth imperatives and issues of social and environmental justice. Indeed, Cho, Hong Kim, and Kim's [56] study on US MSAs demonstrates that neither centralised nor decentralised government structures are effective in narrowing income gaps: addressing one (income inequality) may aggravate the other (economic growth), and vice versa. However, without some coordination above the level of local government, disconnected land-use policies that thwart effective and connected infrastructural development will continue, and strong opposition from local residents and communities to specific forms of enhanced land-use efficiency-e.g., increased densification-will prevail.…”
Section: Political Culture and Identitiesmentioning
confidence: 99%